2009
DOI: 10.1089/jwh.2008.1183
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorders and Obstetric-Gynecologic Care

Abstract: Despite the consequences of EDs and the fact that most physicians agree EDs can negatively impact pregnancy, only about half view ED assessment as their responsibility. Only some weight- and diet-related topics are assessed, and there are gaps in knowledge of ED consequences. Obstetrician-gynecologists are not confident in their training regarding EDs. Improvement in knowledge and altering obstetrician-gynecologists' view of their responsibilities may improve ED screening rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 44 publications
2
38
0
1
Order By: Relevance
“…Healthy eating and weight gain are now routine issues for public health midwives but body image is not routinely considered in antenatal care, despite its potential significance for maternal wellbeing and subsequent weight gain (Leddy et al 2009). Health professionals should be aware that body image concerns, and not just weight itself should be an important element for discussion, given its potential implications for both physical health and wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy eating and weight gain are now routine issues for public health midwives but body image is not routinely considered in antenatal care, despite its potential significance for maternal wellbeing and subsequent weight gain (Leddy et al 2009). Health professionals should be aware that body image concerns, and not just weight itself should be an important element for discussion, given its potential implications for both physical health and wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer than half of obstetricians/gynecologists (ob/gyn) assess eating disorder history, body image concerns, and eating disorder behaviors, despite assessing related constructs of body weight, BMI, exercise, and dietary practices (Leddy et al 2009). Lack of training in identification of signs and symptoms, a perception that assessment falls outside the scope of practice, and lack of awareness of the consequences of eating disorders in pregnancy may explain this (Leddy et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As such, this group may have different knowledge or practice patterns than the nationwide sample of OB/GYNs. Although this study is unable to address this concern directly, there is evidence from a wide range of recent studies that reported clinical practice patterns do not significantly differ between CARN and non-CARN samples (e.g., Anderson, Stumpf & Schulkin, 2009;Bettes et al, 2007;Leddy, Jones, Morgan, & Schulkin, 2009;Morgan, Goldenberg, & Schulkin, 2008a, 2008bMorgan, Driscoll, Zinberg, Schulkin, & Mennuti, 2005;Power, Cogswell, & Schulkin, 2006).…”
Section: Discussionmentioning
confidence: 75%